The Dietary Lipid Content Affects the Tissue Gene Expression of Muscle Growth Biomarkers and the GH/IGF System of Pejerrey (Odontesthes bonariensis) Juveniles - Gómez Requeni, Pedro (2019)
Gene expression of growth hormone receptors (GHRs), insulin-like growth factors (IGFs), myostatin (MSTN) and myogenin (MyoG) was analyzed in juveniles pejerrey fed with graded levels of lipids (L): 6% (L6), 10% (L10), 25% (L25). After 14 weeks, no changes were found in liver GHR-I GHR-II and IGF-II mRNA levels whereas IGF-I decreased in L10 and L25. Muscle GHR-I gene expression increased in L25 whereas GHR-II, IGF-II and MyoG were higher in L6. IGF-I and MSTN expression was not affected by the different diets. Adipose IGF-I mRNA levels decreased in L10. Correlations between body weight and members of GH/IGF system in liver and skeletal muscle were found only in L10 group. Correlations found in L10 group between both liver and skeletal muscle GHR-I and IGF-I were lost in either L6 or L25 groups. Thus, fish fed with apparently unbalanced dietary lipid contents (6% and 25%) exhibit a compensatory regulation of systemic and local components of the GH/IGF axis. Furthermore, the marked inhibition of muscle MyoG gene expression in L25 might limit excessive lipid deposition and fish growth. Our data suggest that a dietary lipid contents of 10% would promote a particular adjustment of the endocrine and autocrine/paracrine GH/IGF system, stimulating body growth and perhaps muscle hyperplasia. On the other hand, a higher dietary lipid content would uncouple the GH/IGF system, reducing hepatic IGF-I, while slightly increasing hepatic GHR-I, probably to prompt lipolysis.